2014
DOI: 10.5713/ajas.14.0312
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production from Vietnamese Animal Manure, Plant Residues and Organic Waste: Influence of Biomass Composition on Methane Yield

Abstract: Anaerobic digestion is an efficient and renewable energy technology that can produce biogas from a variety of biomasses such as animal manure, food waste and plant residues. In developing countries this technology is widely used for the production of biogas using local biomasses, but there is little information about the value of these biomasses for energy production. This study was therefore carried out with the objective of estimating the biogas production potential of typical Vietnamese biomasses such as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 24 publications
4
26
3
2
Order By: Relevance
“…here)As lignin is non-degradable under anaerobic conditions(Triolo et al 2011), lignin shows to be inversely correlated to BMP, which was also observed byTriolo et al (2011) andDandikas et al (2014) using energy crops andCu et al (2015) using plant residues and animal manure. Although the correlation between measured and predicted BMP using only lignin in this study is quite low (R 2 = 0.023), due perhaps to the very low concentration of lignin in all the samples, the model precision estimated by standard error is fairly fine.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…here)As lignin is non-degradable under anaerobic conditions(Triolo et al 2011), lignin shows to be inversely correlated to BMP, which was also observed byTriolo et al (2011) andDandikas et al (2014) using energy crops andCu et al (2015) using plant residues and animal manure. Although the correlation between measured and predicted BMP using only lignin in this study is quite low (R 2 = 0.023), due perhaps to the very low concentration of lignin in all the samples, the model precision estimated by standard error is fairly fine.…”
supporting
confidence: 63%
“…However, there is a relationship between methane yield and the type of organic matter found in substrate. Some studies have successfully found this relationship by building mathematical regression models that compare the organic matter and the amount of methane produced (Buffiere et al, 2006;Cu et al, 2015;Dandikas et al, 2014). However, none of them has used FVW as a single substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas produced from the animal farm manure anaerobic fermentation is primarily composed of methane (CH 4 ) and carbon dioxide (CO 2 ), with smaller amounts of ammonia (NH 3 ), hydrogen (H 2 ), nitrogen (N 2 ), carbon monoxide (CO), saturated water or halogenated carbohydrates [1,2]. Biogas has a high heating value of between 15 and 30 MJ/Nm 3 so it is an attractive source of energy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even if liquid DE had already fermented in an anaerobic process by bio-gas plant (Cu et al, 2015), there remained slight odor in the solution. In the present study, we maintained almost 30 days of rest period after foliar application of liquid DE was carried out at the post-grazing in each paddock and herbage consumption was not significantly different between DE and CF plot in either year.…”
Section: Effect Of Spraying Liquid De To Leafage Of DL Napier Grass Omentioning
confidence: 99%